To work, to retire - or both? Labor market activity after 60 - Mona Larsen; Peder J. Pedersen (IZA Journal of European Labor Studies, 2013)
The Danish labor market follows the trend in other countries of increasing labor force participation in the 60+ group. In Denmark, this increase has - until now - been most pronounced among 60-64-year-olds and among women. Increasing labor force participation is related to both a decline in the take-up of early retirement among 60-64-year-olds, an increase in the average age of entry to a retirement program, and an increase in the propensity of working after entering a retirement program. Significant impact on work after 60 is found from education, gender, marital status, home ownership, aggregate unemployment before retirement, age and education.
Keywords: H55; J14; J26; 330; Labor force participation; Retirement